Intravenous lipid infusion and total plasma fatty acids positively modulate plasma acylated ghrelin in vivo. Issue 3 (June 2017) - Barazzoni, R.; Gortan Cappellari, G.; Semolic, A.; Ius, M.; Dore, F.; Giacca, M.; Zanetti, M.; Vinci, P.; Guarnieri, G.
Summary: Background & aims: Ghrelin is a gastric orexigenic hormone whose activating acylation plays a relevant role in the regulation of energy balance. Nutritional modulators of ghrelin acylation and plasma acylated ghrelin (AG) concentration remain however largely undefined. We aimed at investigating whether circulating free fatty acids (FFA) contribute to regulate plasma AG and its ratio (AG/TG) to total hormone (TG). Methods: Plasma FFA, TG, AG and AG/TG were measured in a primary outpatient care setting in a community-based population cohort of 850 individuals (age 54 ± 10 years, M/F: 408/442) from the North-East Italy MoMa study. 150-min intravenous lipid infusions in rodents (10% lipids, 600 μl/h) were used to investigate the potential causal role of FFA in the regulation of plasma ghrelin profile. Results: Plasma FFA were associated positively with AG and AG/TG while negatively with TG (P < 0.01). Associations between FFA, AG and AG/TG remained statistically significant (P < 0.02) in multiple regression analysis including HOMA insulin resistance and metabolic confounders, and both AG and AG/TG but not TG increased through plasma FFA quartiles (P < 0.01). Consistent with these findings, intravenous lipid infusion with plasma FFA elevation caused elevations of AG and AG/TG (P < 0.05) with no TG modifications. Conclusions: The current findings demonstrate a novel role for circulating FFA availability to up-regulate plasma AG, which could involve FFA-induced stimulation of ghrelin acylation.